Broadband Achromatic Hybrid Metalens Module with 100° Field of View for Visible Imaging - Peixuan Wu; Xingyi Li; Yuanyuan Xing; Jiaojiao Wang; Wujie Zheng; Zekun Wang; Yaoguang Ma (Sensors)
Conventional metalenses struggle with chromatic aberration and narrow field of view (FOV), making it challenging to meet the dispersion requirements for large apertures and compensate off-axis aberrations for wide FOV. Here, we demonstrate a hybrid metalens module consisting of five refractive plastic lenses and a polarization-insensitive metalens to achieve broadband achromatic imaging within 400–700 nm and a wide FOV up to 100°. The system exhibits negligible variation in focal length (~1.2%) across the visible range (460–656 nm) and consistently achieves modulation transfer function (MTF) values > 0.2 at 167 lp/mm across all wavelengths and incident angles. We also demonstrate integrated lens modules that capture high-quality images from distances ranging between 0.5 and 4 m without post-processing, showcasing its potential for compact, wide-angle optical systems.